KEMAMPUAN MENULIS KEMBALI ISI CERPEN “SEPOTONG BURGER” KARYA SANICE ALFIETA OLEH SISWA KELAS IX SMP N I SEI KANAN LABUHAN BATU SELATAN TAHUN PEMBELAJARAN 2012/2013 - Junaina Umairi (Basastra, 2013)
Writing is a very important skill in life, are not only important in education, but also very important in people's lives. As soon as  re-write the contents of the short story, students should be able to understand the way of story is written by the author, from the beginning to understand the intrinsic elements and understand the meaning of difficult words contained in a short story. The ability of the students' understanding after reading the short story can be known by asking students to retell or rewrite the content of the short stories that have been read by using their own language. Keywords, Writing, Short Story